The humanities and public life - Brooks, Peter, 1938-; Jewett, Hilary (Fordham University Press, 2014)
This work tests the proposition that the humanities can, and at their best do, represent a commitment to ethical reading. And that this commitment, and the training and discipline of close reading that underlie it, represent something that the humanities need to bring to other fields: to professional training and to public life.